The Canadian Unemployment Insurance Generosity: Reflections From A Comparative Analysis - Amine, Samir (Comparative Economic Research. Central and Eastern Europe, 2016)
The unemployment compensation system is at the centre of the current economic and political debate in many Western countries which, under the effects of the increase in public debt, must decide the level of their unemployment insurance while taking into account its impact on the performance of the labour market. In this article, we compare the generosity of such public policy in France and in Canada, while focusing on the experience of central and eastern Europe. By building a composite index, we show that the French unemployment insurance is more generous only in pecuniary terms, and not in its qualitative dimension.